Bronchobiliary Fistula Localized by Cholescintigraphy with Single-Photon Emission Computed Tomography - Artunduaga, Maddy (World J Nucl Med, 2015)
Biliptysis is an important clinical feature to recognize as it is associated with bronchobiliary fistula, a rare entity. Bronchobiliary fistulas have been diagnosed with planar cholescintigraphy. However, cholescintigraphy with single-photon emission computed tomography (SPECT) can better spatially localize a bronchobiliary fistula as compared to planar cholescintigraphy alone, and is useful for preoperative planning if surgical treatment is required. Here, we present the case of a 23-year-old male who developed a bronchobiliary fistula in the setting of posttraumatic and postsurgical infection, which was diagnosed and localized by cholescintigraphy with SPECT.